Bio-Organically Acidified Product-Mediated Improvements in Phosphorus Fertilizer Utilization, Uptake and Yielding of Zea mays in Calcareous Soil - Khuram Shehzad Khan; Muhammad Naveed; Muhammad Farhan Qadir; Muhammad Yaseen; Manzer H. Siddiqui (Plants, 2023)
The demand for a better agricultural productivity and the available phosphorus (P) limitation in plants are prevailing worldwide. Poor P availability due to the high pH and calcareous nature of soils leads to a lower P fertilizer use efficiency of 10–25% in Pakistan. Among different technologies, the use of biologically acidified amendments could be a potential strategy to promote soil P availability and fertilizer use efficiency (FUE) in alkaline calcareous soils. However, this study hypothesized that an acidified amendment could lower soil pH and solubilize the insoluble soil P that plants can potentially uptake and use to improve their growth and development. For this purpose, the test plant Zea mays was planted in greenhouse pots with a recommended dose rate of 168 kg ha−1 of P for selected phosphatic fertilizers, viz., DAP (diammonium phosphate), SSP (single superphosphate), and RP (rock phosphate) with or without 2% of the acidified product and a phosphorus solubilizing Bacillus sp. MN54. The results showed that the integration of acidified amendments and PSB strain MN54 with P fertilizers improved P fertilizer use efficiency (FUE), growth, yield, and P uptake of Zea mays as compared to sole application of P fertilizers. Overall, organic material along with DAP significantly improved plant physiological-, biochemical-, and nutrition-related attributes over the sole application of DAP. Interestingly, the co-application of RP with the acidified product and MN54 showed a higher response than the sole application of DAP and SSP. However, based on our study findings, we concluded that using RP with organic amendments was a more economically and environmentally friendly approach compared to the most expensive DAP fertilizer. Taken together, the current study suggests that the use of this innovative new strategy could have the potential to improve FUE and soil P availability via pH manipulation, resulting in an improved crop productivity and quality/food security.